Chapter 2.3 Fostering attentional awareness for connectedness, with agility and empathy as core values - Seago, Catherine (Taylor & Francis, 2024)
This chapter considers how dance technique practice can foster an agile and empathetic use of attention. It builds upon a recent action research project exploring how attention is commonly viewed and valued in dance training and how a bricolage-style approach to classes can encourage inter-connectedness with others, as well as amongst ideas and practices. Drawing on ideas of flow (Csikszentmihalyi, Claxton) this chapter argues that greater awareness of how we attend in practicing physical agility together can help dancers to develop an ethical agility through being present and sensitive to all that is happening in the dance class. The discussion reflects on the ways in which interconnectedness can be cultivated through an agile and empathetic use of attention and the implicit value of realising connections within and beyond dance skills development.